Etude Mineralogique Des Fractions Sableuse Et Argileuse Du Remplissage Du Gisement De Montgaudier, Charente, France - Mohammed, Boukhir; Abdel-Ali, Chaouni; Abderrahim, Lahrach (European Scientific Journal, ESJ, 2017)
The mineralogical investigation of sand fraction of different sectors of filling of Montgaudier deposit revealed that heavy minerals are mainly composed of amphiboles and disthene in all analyzed samples. The other mineralogical species encountered appear having only a secondary role in the composition of heavy mineral processions. These minerals are: Andalusite, brookite, chlorite, epidote, garnet, pyroxene, rutile, sillimanite and sphene. The opaque minerals are relatively numerous in all the studied samples which they are in different stages of alteration, associated with other minerals presenting a fresh appearance. The light minerals consist mainly of hyaline or translucent quartz grains and milky or opalescent grains. The study of clay minerals generally showed a predominance of kaolinite in all sectors, followed by illite and chlorite. Smectite comes in only fourth place. This cortege is complemented by interstratified smectite-chlorite, which are very poorly represented. The mineralogical study of the deposits at the different parts of the layers filling of the Montgaudier deposit and the sediments in the immediate vicinity permitted to determine the origin of these deposits. Their procession is largely influenced by the geological nature of the Tardoire watershed but also of the mineralogical composition of the surrounding rock in which this cave was.